Comparative efficacy and safety of targeted therapy and immunotherapy for HER2-positive breast cancer: a systematic review and network meta-analyses - Gu, Suyu; Liu, Yuting; Huang, Yufan; Lin, Wenzheng; Li, Ke (Frontiers in Oncology, 2024)
Background In recent years, novel therapies targeting specific molecular pathways and immunotherapies have exhibited promising outcomes for treating human epidermal growth factor receptor 2 (HER2)-positive breast cancer. Our work aimed to assess the effectiveness and safety of these emerging treatment regimens for this disease. Material and methods We systematically searched databases including PubMed, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials their inception to August 2023 to identify relevant randomized controlled trials (RCTs). The quality of eligible RCTs was evaluated with the Cochrane risk-of-bias tool, version 2 (RoB2). Investigated outcomes encompassed progression-free survival (PFS), overall survival (OS), disease-free survival (DFS), pathologic complete remission (pCR), and adverse events (AEs). They were expressed as hazard ratio (HR) with 95% conference intervals (CI) or risk ratio (RR) with 95% CI. Results Our analysis identified a total of 28 RCTs suitable for inclusion in the NMA. Regarding the PFS, all these treatment regimens exhibited comparable effectiveness. In terms of OS, Capecitabine+Trastuzumab, Lapatinib+Trastuzumab and Pyrotinib+Capecitabine exhibited better effect compared to other treatments. Regarding pCR and AEs, all these treatment regimens exhibited comparable effectiveness, especially Lapatinib+Trastuzumab and Pyrotinib+Capecitabine. Conclusion Our study highlights the prominent role of targeted therapies and immunotherapies in treating HER2-positive breast cancer. The efficacy of trastuzumab-containing regimens was superior to other treatment options, while maintaining a comparable safety profile. Based on these findings, trastuzumab-containing regimens emerge as a preferable and recommended choice in clinical practice for managing HER2-positive breast cancer. Systematic Review Registration PROSPERO, identifier CRD42023414348.